A high temporal-spatial vehicle emission inventory based on detailed hourly traffic data in a medium-sized city of China. (May 2018) - Liu, Yong-Hong; Ma, Jin-Ling; Li, Li; Lin, Xiao-Fang; Xu, Wei-Jia; Ding, Hui
Abstract: To improve the accuracy and temporal-spatial resolution for a vehicle emission inventory in a medium-sized city with a strip road network, this study was conducted based on detailed hourly traffic-flow data for each day of 2014, and covered all road types and regions in the city of Foshan. Detailed hourly emission characteristics and sources in five regions were analysed. The results showed that the total vehicle emissions of CO, NOX, VOCs, and PM2.5 were 13.10 × 10 4, 0.23 × 10 4, 4.46 × 10 4, and 0.18 × 10 4 tons, respectively. Motorcycles (MCs) and light passenger cars (LPCs) were the dominant contributors of CO emissions, while buses and heavy passenger cars (HPCs) were the dominant contributors for NOX . As a whole, the daytime contributions to total emissions were close to 80%, and emissions during the peak periods accounted for almost 40%. Specifically, the hourly emissions of each pollutant on workdays were higher than on non-workdays (maximum up to 64.2%), and for some roads the early peak periods changed significantly from workdays to non-workdays. At expressways, artery roads, and local roads, the daily emission intensities of CO, NOx, and PM2.5 in Foshan were close to or even higher than that of Beijing. On a regional scale, the temporal variation of vehicle emissions on workdays at artery roads of different regions were similar. In addition, the higher emission intensities of CO and VOCs were identified in DaLiang-RongGui (DLRG) and that of NOX and PM2.5 were in Central Region (CR). These results are meaningful for decision-makers to help provide more detailed vehicle pollution control measures in Foshan with a strip road network and only one ring road. Graphical abstract: Image 1 Highlights: Total emissions and the emissions during the peak periods were calculated. The dominant contributors of pollutant emissions were revealed. The hourly emissions of each pollutant on workdays were higher than on non-workdays. The vehicle emissions in Foshan were dispersed in different regions. Abstract : The work establishes a basis for further research that evaluates the impacts of emission reduction policies in medium-sized cities with a strip road network and only one ring road.